Promising field electron emission performance of vertically aligned one dimensional (1D) brookite (beta) TiO2 nanorods - Devan, Rupesh S.; Ma, Yuan-Ron; More, Mahendra A.; Khare, Ruchita T.; Antad, Vivek V.; Patil, Ranjit A.; Thakare, Vishal P.; Dhayal, Rajendra S.; Schmidt-Mende, Lukas (RSC Advances, 2016)
We evidence field-electron emission (FE) studies on the large-area array of one-dimensional (1D) brookite (beta) TiO2 nanorods. The pure 1D beta-TiO2 nanorods of 10 nm width and 760 nm long were synthesized on Si substrate utilizing hot-filament metal vapor deposition technique. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis evidenced the beta-TiO2 nanorods to be composed of orthorhombic crystals in brookite (beta) phase. X-ray photoemission spectroscopy (XPS) revealed the formation of pure stoichiometric (i.e. 1 : 1.98) 1D TiO2 nanorods. The values of turn-on field, required to draw current density of 10 mA cm(-2), was observed 3.9 V mu m(-1) for pristine 1D beta-TiO2 nanorods emitters, which were found significantly lower than doped/undoped 1D TiO2 nanostructures (i.e. nanotubes, nanowires, nanorods) based field emitters. The enhanced FE behavior of the TiO2/Si emitter can be attributed to modulation of electronic properties due to the high aspect ratio of vertically aligned TiO2 nanorods. Furthermore, the orthodox emission situation of pristine TiO2/Si emitters exhibit good emission stability and reveal their potentials as promising FE material.